Detection and Detoxification of Aflatoxin B1 from Fish Feedstuff Using Microwave and Ozone Gas - Hassan, Fadia Falah; Hussein, Halima Zugher; Hawar, Sumaiya Naeema (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The current study was designed to investigate the occurrence of aflatoxin B1 in thirty two samples of fish feedstuff were collected randomly from some Iraqi local markets using ELISA technique. Aflatoxin B1 was detected in thirty samples and the concentration of toxin ranged from 50 ppb to 1000 ppb. Microwave and ozone were used for detoxification of aflatoxin B1 from sample with highest concentration (1000 ppb), two degree of temperature and two times (50°C and 100°C for 5 minute and 10 minute to each degree) of microwave, also two doses and two times (2 g and 4 g for 5 minute and 10 minute to each dose) of ozone gas were used. Degradation of aflatoxin B1 by microwave has been found to cause a significant (P ≤ 0.05) decrease of aflatoxin B1, Moreover, the concentration of aflatoxin B1 was dependent on temperature degrees and exposure time, also sample subjected to ozone gas caused a significant (P ≤ 0.05) decrease in aflatoxin B1 contents and the concentration of aflatoxin B1 was dependent on doses and times of exposure. Results showed that ozone gas was more effective in aflatoxin B1 reduction when compared with microwave.